Instrument Development for Perceptions of Medical Teachers about Integrated Curriculum - Kayani, Ziyad Afzal (International Journal of Pathology, 2022)
Background; Instrument is any device the researcher uses to collect information, such as a rating scale or a questionnaire. Their use is an important method of data collection and they have been used extensively in studies. The design and validation of instruments is neglected in many studies and it often leads to an inability to compare data among various studies. Weather a questionnaire or an interview guide is used to collect data its reliability and validity has to be maintained through a series of steps starting from defining constructs then generating items followed by piloting and lastly finalizing the scale.Objective: This study aims to develop data collection instrument using the steps mentioned to obtain perceptions of medical teachers about integrated curriculum.Methods: A thorough literature search and critical appraisal of selected articles was done and items were identified. Four essential steps were followed and a panel of experts validated the instrument.Results: Content and construct of the instrument was defined. Items were generated incorporating the content. In the questionnaire closed ended items were formulated for quantitative analysis. In the interview guide to be used for qualitative analysis semi structured open ended items were developed. Known groups method was used to support construct validity of instruments. Scale was finalized after validation by panel of experts.Conclusion: For getting perceptions of medical teachers about integrated curriculum a standard instrument should be used. We have developed instruments which are valid and reliable and their use in future research will improve comparability among different studies.